(untitled) - Simpson,Wes (Amsterdam ; Boston, 2006)
Video Over IP gives you everything you need to know to choose from among the many ways of transferring your video over a network. The information is presented in an easy to read format, with comparison charts provided to help you understand the benefits and drawbacks of different technologies for a variety of practical applications.
Keywords: TCP/IP (Computer network protocol),Digital video,Telecommunication,Giao thức mạng máy tính; Data processing